Export/import procedures and documentation - Johnson, Thomas E., 1948- (AMACOM, 2002)
Annotation The fourth edition of the reference for export/import professionals is revised to include new forms and instructions, new US Customs Service checklists, and new Automated Export System procedures. It overviews the entire export/import process and provides ready-to-use forms with instructions, cost-saving shortcuts, and tips on building a better operation. A training manual for new employees is included, plus a quick course on advanced techniques for more experienced professionals. There is also a glossary of 250 international trade terms. New to this edition is a section on e-commerce in international marketing, listings for export and import software, and a list of Web sites for 94 export and import agencies and information sources. Johnson is a partner in an international trade law firm. Annotation copyrighted by Book News, Inc., Portland, OR.
Title from e-book title screen (viewed Sept. 19, 2008).
Keywords: Export marketing -- United States.; Exports -- United States -- Forms.; Imports -- United States -- Forms.; Foreign trade regulation.; International trade.; elektronické knihy; electronic books